10 Am2/imd secretion from human pulmonary smooth muscle cells and pulmonary fibroblasts is augmented in response to mechanical stretch. (26th March 2018) - Thomas, Gavin; Harbinson, Mark T; McVeigh, Gary; Watson, Christopher; Campbell, Malcolm; Cheung, Alice; Bell, David
Abstract : Introduction: Pulmonary hypertension (PHT) is a severe life-limiting condition resulting in progressive shortness of breath, exercise intolerance and heart failure. PHT is defined by increased mean pulmonary arterial pressure (PAP) ≥25 mmHg at rest, and has been attributed to an imbalance between vasodilator and vasoconstrictor influences in the pulmonary microcirculation. Assessment of the vasodilator AM2/IMD, a member of the CGRP/AM peptide family, may have potential application as novel disease biomarker. Objective: To quantify secretion of AM2/IMD from human pulmonary vascular cells cultured under basal, simulated normotensive and hypertensive conditions. Methods: Pulmonary fibroblasts (PF), pulmonary smooth muscle (PSM), human pulmonary artery endothelial cells (HPAEC) and human pulmonary microvascular endothelial cells (HPMEC) were cultured on silicone elastomer-bottomed Flexcell plates pre-coated with Matrigel at rest (un-flexed) or subjected to cyclic mechanical stretch (Flexcell Strain Unit) to simulate pulmonary normotensive (15 mmHg, 2.0 kPA) and hypertensive (40 mmHg, 5.3 kPA) conditions at a frequency of 1 Hz (60 cycles per minute) for 48 hour. AM2/IMD was extracted from the medium of cultured cells and quantified by ELISA (Phoenix Pharmaceuticals Inc. Karlsruhe, Germany). Results: Concentrations of AM2/IMD in culture medium from cells incubated under various conditions were as follows: ng.ml -1, mean ±SE, n=2–12; *difference relative to un-flexed, p<0.05; +difference between normotensive and hypertensive condition. Conclusion: Cyclic stretch enhanced secretion of AM2/IMD from PF and PSM, indicating that these cells may be an important source of this vasodilator peptide in the pulmonary microcirculation under physiological conditions. Secretion was not augmented in hypertension relative to normotensive conditions. AM2/IMD is unlikely therefore to be a suitable diagnostic or prognostic biomarker in PHT.